Efficacy and Safety of Endoscopic Esophageal Dilatation in Pediatric Patients with Esophageal Strictures - Hasan M. A. Isa; Khadija A. Hasan; Husain Y. Ahmed; Afaf M. Mohamed (International Journal of Pediatrics)
Background and Objectives. Benign strictures are the main cause of esophageal strictures in children. They can be managed by different modalities but endoscopic dilatation is the standard therapy. This study is aimed at reviewing the efficacy and safety of endoscopic dilatations in children with esophageal strictures. Materials and Methods. In this retrospective cross-sectional single center study, records of patients with esophageal strictures presented to the pediatric department, Salmaniya Medical Complex, Bahrain, in the period between 1995 and 2019 were reviewed. Demographic data, indications of endoscopic dilatations, the procedure success rate, and possible complications were assessed. Results. Forty-six children were found to have esophageal strictures. Twenty-five (54.3%) patients were males. Most patients presented during infancy (86.5%, 32/37 patients). Twenty-six (56.5%) patients required 88 dilatation sessions, while the remaining 20 (43.5%) patients did not require dilatations. The median number of dilatation sessions per patient was three (interquartile range=2–5). Savary-Gilliard bougienages were the main dilators used (80.8%, 21/26 patients). Anastomotic stricture (post esophageal atresia/tracheoesophageal fistula repair) was the main cause of esophageal strictures and was found in 35 (76.1%) patients. Patients with nonanastomotic strictures had more frequent dilatations compared to those with anastomotic strictures (P=0.007). The procedure success rate was 98.8%. Yet, it was operator dependent (P=0.047). Complete response to dilatation was found in 18 (69.2%) patients, satisfactory in seven (26.9%), and an inadequate response in one (3.9%). Those with satisfactory responses still require ongoing dilatations based on their symptoms and radiological and endoscopic findings. No perforation or mortality was reported. Patients with dilatations had more recurrent hospitalization (P<0.0001), more dysphagia (P=0.001), but shorter hospital stay (P=0.046) compared to those without dilatations. Surgical intervention was required in one patient with caustic strictures. The median follow-up period was six years (interquartile range=2.25–9.0). Conclusions. Endoscopic esophageal dilatation in children with esophageal strictures is effective and safe. Yet, it was operator dependent. Nonanastomotic strictures require more dilatations compared to anastomotic strictures. Findings of this study are comparable to those reported worldwide.